Police Prevention Units in Poland from 1918 to Modern Times - Robert Czarniawski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The police forces are an indispensable element in upholding security and public order in a state, both on daily bases and in states of emergency. The evolution of the Polish police forces begins in 1918 with restoration of the country’s sovereignty after 123 years of partitions. Since that time the organisational structure, functioning and the scope of tasks performed by the Police have evolved and developed due to social, political and economical changes in order to keep up with constantly changing reality and to improve efficiency of operations performed with respect to maintaining security and public order.